The use of Home Assignment Method to Improve the Understanding of Learning Materials for Students at Sanggar Bimbingan Sungai Mulia 5 Malaysia - Cahya Hidayati; Rimma Regita Cahyani; Murfiah Dewi Wulandari; Suryanto Nugroho (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Peguruan Tinggi Muhammadiyah dan Aisyiyah, 2023)
Learning is a very important process in human life. This process allows someone to acquire knowledge, skills, and attitudes needed to actively participate in society and achieve their life goals. Assignment method is the way teachers give tasks to students to complete. Assignment method is one of the popular learning methods in many educational institutions because it can help students learn independently and enhance their social skills. Home assignment methods have the potential to improve students' understanding of the learning material. Children's understanding is further enhanced through the use of home assignment methods